Homelessness and Sexual Identity Among Middle School Students. (August 2015) - Rice, Eric; Petering, Robin; Rhoades, Harmony; Barman‐Adhikari, Anamika; Winetrobe, Hailey; Plant, Aaron; Montoya, Jorge; Kordic, Timothy
ABSTRACT BACKGROUND Lesbian, gay, bisexual, or questioning (LGBQ) high school students experience higher rates of homelessness than their heterosexual peers. Moreover, LGBQ high school students are more likely to stay in riskier locations (eg, with a stranger) and less likely to stay in a shelter. This study tested whether these trends also apply to middle school students. METHODS Using representative data, we examined sexual identity and homelessness among Los Angeles Unified School District middle school students. RESULTS Nearly 10% of middle school students identified as LGBQ and 23.5% experienced at least 1 night of homelessness during the previous year. Contrary to high school data, LGBQ students did not experience higher rates of homelessness overall. However, when limiting the sample to students who had experienced homelessness, LGBQ students were more than 5 times as likely as heterosexual students to have stayed in a public place and 63% as likely to have stayed in a shelter. CONCLUSIONS Lesbian, gay, bisexual, or questioning students are more likely to experience public homelessness. Schools must implement homelessness surveillance systems to assist in identifying early episodes of homelessness, thereby reducing the likelihood of poor physical and mental health outcomes associated with chronic homelessness.